THE MAIN FUNCTION OF EDUCATION, TRAINING AND PERSONALITY FORMATION IN THE SYSTEM OF PEDAGOGICAL SCIENCES (INTERNATIONAL JOURNAL OF SCIENCE AND TECHNOLOGY, 2025)
The article shows a methodological service that studies the conditions for teaching special subjects as an important branch of the system of pedagogical sciences. The object of pedagogical science is expanding every year, as a result of which its branches are also divided into several groups, which are called the system of pedagogical sciences. It has been revealed that, as an important branch of the system of pedagogical sciences, it is a systematic science that studies the conditions for teaching special subjects.